THE RISE OF AT-TAQWA AS THE GRAND MOSQUE AND AUTHORITY CONTESTED IN CIREBON-INDONESIA - Didin Nurul Rosidin; Asep Saefullah; Ihsan Sa'dudin (Journal of Islamic Architecture, 2022)
This study aims to elaborate on the rise of The At-Taqwa Grand Mosque as the Jami' mosque and the long-standing great mosque of Sang Cipta Rasa in Cirebon, West Java, in 1963. The emergence of the At-Taqwa not only drove the rise of new Jami mosques in the Cirebon in the following years but also brought about the contestation of religious authority since mosques function as a source of religious authority in Islam. The study rests on the history of the Great Mosque of Sang Cipta Rasa as the first Jami Mosque in Cirebon, the emergence of the At-Taqwa as the Grand Mosque, and the implications of the two Jami mosques in the context of contesting the authority of religiosity in the Muslim community in Cirebon. The method used in this study is based on a historical analysis approach. The study shows that the Sang Cipta Rasa enjoyed as the source of religious authority in Cirebon and neighborhood areas for an extended period. However, the rise of the Grand Mosque of At-Taqwa also diminished the stature of the Sang Cipta Rasa mosque as the sole source of religious authority. On the other hand, it further strengthened the spreading of their authority in Cirebon based on mosques.